Effects of dietary supplemental chromium methionine, zinc oxide, and ascorbic acid on performance, egg quality traits, and blood parameters of laying hens subjected to heat stress - Mozhdeh Karami; Mehran Torki; Hamed Mohammadi (Journal of Applied Animal Research, 2018)
Based on a 2 × 2 × 2 factorial, the effects of three dietary supplemental including chromium methionine (Cr) (0 and 400 μg/kg diet), zinc oxide (Zn) (0 and 30 mg/kg diet), and vitamin C (VitC) (0 and 250 mg/kg diet) on egg production (EP) and mass (EM) and egg traits in heat-stressed (HS) Lohmann LSL-Lite laying hens from 30 to 45 weeks of age were evaluated. The house temperature was kept at 18°C (weeks 30–40 of age) and then increased to 32°C (weeks 41–45 of age). Dietary treatments had no significant effects on EP, egg weight, EM, and feed conversation ratio before and after exposure to heat stress (P > 0.05). Decreased feed intake intake was observed in group of VitC during exposing to HS (P < 0.05). Dietary supplemental Cr decreased serum glucose concentration before HS (P < 0.05). A combination of Cr and VitC increased serum glucose concentration before and during HS (P < 0.05). Decreased serum concentration of Zn was detected in hens fed the diets with VitC, Cr, or Zn (P < 0.05). Increased serum concentration of Cr was observed in hens fed the diets supplemented with Cr (P < 0.05).